Efektivitas Model Pendampingan Pemeriksaan Payudara Sendiri (SADARI) Remaja Putri SMAN-1 Katingan Tengah - triska febriyani; Seri Wahyuni; Itma Annah (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2023)
The World Health Organization (WHO) in 2018 stated that 61.16% of 103 or around 63 women aged 10-24 years died in Indonesia due to breast cancer. Central Kalimantan Province in 2017 experienced an increase in the discovery of tumors/lumps in the breast from originally 82 people (1.54%) from a sample of 5,313 people in 2016 to 247 people (1.76%) from a sample of 14,063 people in 2017. City of Palangka Raya in 2018 , in early detection of breast cancer there was an increase in 2018 by 8 cases (0.018%) of 444 samples. This study aims to determine characteristics including age, level of education and employment, known average knowledge of BSE before and after intervention using an application, and a more effective breast examination assistance model by measuring the level of BSE knowledge in adolescents at SMAN-1 Katingan Tengah. This research is a research that uses a descriptive method with data analysis used is univariate and bivariate with a two-mean difference test and statistics. The research sample consisted of 30 young women and 30 parents (mothers) using a random sampling technique. The results showed that most of the young women had good knowledge before the intervention of 30.0% with an average of 13.17 and after being given intervention through the application increased to 100% with an average of 19.07 and some parents (mothers) had good knowledge before the intervention 20, 0% with an average of 12.63 and after being given intervention through family assistance increased to 100% with an average of 17.97. Comparison of the average value after the intervention of the effectiveness of the breast self-examination assistance model (BSE) by group with a difference of 1.1. And it is proven statistically where the value is (p = 0.000).